Prakerin: Preparing Vocational School Students for Work - Fitriana Rahmawati (Edunusa: Journal of Economics and Business Education, 2022)
One of the characteristics of vocational education is preparing students to enter the world of work. Vocational education emphasizes "hands on-experience", one of which is obtained through industrial work practice activities (prakerin). The purpose of this research is to conduct a study to identify internship activities as an effort to prepare Vocational High School or Sekolah Menengah Kejuruan (SMK) students for work. The research method used is to use a systematic literature review (SLR). 5 articles were obtained from search results on Google Scholar with the password prakerin and work readiness of SMK students in the 2017 -2022 year range. The results of the study show that vocational students' readiness to work can be pursued with internship activities.